2013
DOI: 10.1080/13639080.2013.805186
|View full text |Cite
|
Sign up to set email alerts
|

But does it work? Reflective activities, learning outcomes and instrumental learning in continuing professional development

Abstract: This paper examines the relationship between reflective practice and instrumental learning within the context of continuing professional development (CPD). It is argued that instrumental learning is a unique process of adult learning, and reflective practice's impact on learning outcomes in instrumental learning contexts remains unclear. A new conceptualisation of instrumental learning in CPD is provided to illustrate the issue's relevance and potential implications. Three justifications for further investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…Organisational demands for evidence of HR development are thus problematic, when different conceptualisations of professional learning (Roessger 2013) are implicit in performance contracts.…”
Section: Sense-making Of Cpdmentioning
confidence: 99%
“…Organisational demands for evidence of HR development are thus problematic, when different conceptualisations of professional learning (Roessger 2013) are implicit in performance contracts.…”
Section: Sense-making Of Cpdmentioning
confidence: 99%
“…I define trades training here as formal on‐the‐job and classroom training to provide learners with current and specialized skills to perform a job. These skills are often specific, demonstrable, and consequential to organization, employee, and client welfare (see Roessger, ). Although not limited to specific industries, trades training programs often serve construction industry occupations such as carpentry, electrical work, pipefitting, masonry, and tile setting.…”
Section: Trades Trainingmentioning
confidence: 99%
“…I define trades training here as formal on-the-job and classroom training to provide learners with current and specialized skills to perform a job. These skills are often specific, demonstrable, and consequential to organization, employee, and client welfare (see Roessger, 2013 ).…”
Section: Trades Trainingmentioning
confidence: 99%
“…The idea that reflection will lead to learning and improvement is based on the work of Dewey from the 1930s and continued with models such as Schön and Gibbs designed to support reflective practice . Whether reflection prompts learning and change has been questioned, although some studies have identified changes in behaviour as a direct result of reflection taking place within clinical practice settings . Reflective practice is now mandated for most health professionals, with documented evidence of reflecting on patient and colleague feedback required for continuing professional development and revalidation.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Whether reflection prompts learning and change has been questioned, although some studies have identified changes in behaviour as a direct result of reflection taking place within clinical practice settings. [17][18][19][20] Reflective practice is now mandated for most health professionals, with documented evidence of reflecting on patient and colleague feedback required for continuing professional development and revalidation. Despite the focus on retrospective written reflection, increasingly, arguments are being made that reflection, and in particular reflection in action, should instead be fully embedded within the multiple contexts of clinical practice.…”
Section: Introductionmentioning
confidence: 99%